Essays in our changing order - Veblen, Thorstein (The Viking Press, 1954)
Essays in Our Changing Order is split into three sections, Essays in Economics, Miscellaneous Papers, and War Essays.Veblen was in reality was one of those rare men who may be said to have been ahead of his time, ahead in the sense that what he said and thought was destined to be accepted by succeeding generations though they were rejected by his own.This early work by Thorstein Veblen was originally published in 1927, we are now republishing it with a brand new introductory biography.